Variation in leaf functional traits of Pinus armandii and their drivers along an altitudinal gradient in Karst mountains - He, Bin; Li, Wangjun; Bai, Xiaolong; Zou, Shun; Li, Qing (Frontiers in Plant Science, 2025)
IntroductionLeaf functional traits are pivotal indicators of plant ecological strategies, reflecting adaptations to environmental conditions. However, the patterns of intraspecific trait variation along environmental gradients and their underlying drivers remain inadequately explored, particularly in fragile ecosystems like karst landscapes.MethodsWe investigated 12 leaf functional traits (encompassing morphological and chemical characteristics) of Pinus armandii along an elevational transect (2128 to 2509 m) in the Karst mountainous region of southwestern China. Using correlation and redundancy analyses, we examined altitudinal trends in trait variation and their relationships with key soil factors.ResultsOur results revealed substantial intraspecific variability in all leaf traits, with coefficients of variation ranging from 3.24% to 28.15%. Specific leaf area, leaf length, thickness, area, carbon content, potassium content, and the ratios of C:N, C:P, and N:P decreased significantly with increasing elevation. Conversely, leaf dry matter content, nitrogen content, and phosphorus content increased significantly. We found notable coordination and trade-offs among traits, forming an integrated network centered on the C:N ratio. Soil factors—specifically soil organic carbon, pH, and available potassium—were identified as the primary drivers of this trait variation.DiscussionP. armandii in karst mountainous regions adapts to elevational changes through coordinated adjustments in leaf functional traits, thereby optimizing resource acquisition and use strategies. These findings advance our understanding of plant adaptation mechanisms in such fragile environments.